Response of Some Rice Cultivars in New Opening Paddy Fields with High Fe2+ Using Multi-packet Technology - M Zulman Harja Utama; Ismed Wahidi; . Sunadi (JOURNAL OF TROPICAL SOILS, 2012)
The main obstacle to increase rice yield in new opening paddy fields, is that high levels of dissolved ferrous ions(Fe2+) which toxic to plants. This research aimed to study the growth and yield of several rice cultivars tolerant toFe2+ in the new opening paddy fields with multi-packet technology. The experiment was conducted from April toDecember 2010, at the new opening pay fields in Koto Baru of Dharmasraya District, West Sumatra. Experimentsused a factorial in a Completely Randomized Design with three replications. The first factor was, selected ricevarieties which were: Krueng Aceh; IR 36; Tukad Balian; Ciherang; and Cisokan. The second factor was thedifferent plant spacing which were a 30 × 30 cm with two seeds per hole, and Plant spacing (10 × 10) × 30 × (10 × 10)cm with one seed per hole. The rice cultivation with packet technology can improved the growth and yield of paddyrice cultivated in new opening paddy field high in Fe2+. Technology package consisting a combination of ricevariety (Krueng Aceh, IR36, and Tukad Balian) + SRI system + peat amelioran 20 Mg ha-1 + plant spacing (10 × 10)× 30 × (10 × 10) cm with one seed per hole, had the best growth and yield of rice cultivated in the new opening fieldshigh in Fe2+, especially in Koto Baru of Dharmasraya District, Krueng Aceh was a variety with the highest grain production by 5.65 Mg ha-1.Keywords: Fe2+; new fields; rice cultivar; technology[How to Cite: Utama MZH, I Wahidi and Sunadi. 2012. Response of Some Rice Cultivars in New Opening Paddy Fields with High Fe2+ Using Multi-packet Technology. J Trop Soils, 17 (3) : 234-244. doi: 10.5400/jts.2012.17.3.239][Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.3.239]